2021
DOI: 10.1155/2021/9286492
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Para and Perirenal Fat and High-Density Lipoprotein and Its Function in Patients with Type 2 Diabetes Mellitus

Abstract: Background. Para and perirenal fat is a fat pad surrounding the kidneys. Recent studies showed the association between para and perirenal fat and cardiovascular diseases including atherosclerosis and hypertension. We aimed to assess the relationship between para-perirenal ultrasonographic fat thickness and serum high-density lipoprotein (HDL) level and cholesterol efflux capacity of HDL in patients with type 2 diabetes mellitus (T2DM). Methods. We recruited 58 subjects with T2DM and collected anthropometric in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Numerous studies have shown that obesity indicators are associated with metabolic risk factors, while many studies have mainly focused on PRFT [ [23] , [24] , [25] ]. Ke J et al showed a negative correlation between PRFT and HDL-c [ 26 ], which was consistent with our findings. It's reported that dyslipidemia is one of the risk factors for renal dysfunction [ [27] , [28] , [29] ].…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have shown that obesity indicators are associated with metabolic risk factors, while many studies have mainly focused on PRFT [ [23] , [24] , [25] ]. Ke J et al showed a negative correlation between PRFT and HDL-c [ 26 ], which was consistent with our findings. It's reported that dyslipidemia is one of the risk factors for renal dysfunction [ [27] , [28] , [29] ].…”
Section: Discussionsupporting
confidence: 93%
“…21 Ke et al found that PrFT was negatively correlated with the serum HDL-c level and positively correlated with cholesterol efflux capacity in T2DM. 22 In addition, several observational studies also revealed that increased PrFT was positively associated with increased WC and HOMA-IR. 8,23,24 The effects of VAT on metabolic dysfunctions and inflammation have been reported previously.…”
Section: Discussionmentioning
confidence: 99%